PEMANFAATAN LIMBAH SEKAM PADI UNTUK PEMBUATAN KOMPOSIT HAMBAT PANAS MENGGUNAKAN MATRIK RESIN - Ngafwan, Ngafwan (Media Mesin: Majalah Teknik Mesin, 2006)
The paddy husk is often used as material for persevering ice block which means it has good thermal resistance property. The thermal resistance of paddy husk can be used as base for composing new composite material having good thermal resistance property. The material is made by using polyester as binder with composition paddy husk and polyester in 20%, 30%, 40%, 50% and 60% of husk volume fraction. The types of composite manufactured are honeycomb and nonhoneycomb composites. The only test that has been carried out is thermal conductivity property. The thermal conductivity decreases as material temperature increases. In honeycomb composite the decrease of thermal conductivity occurred greater than that in non-honeycomb composite.